'Our courage has grown': a grounded theory study of enablers and barriers to community action to address violence against women in urban India. Issue 1 (23rd January 2023) - Gram, Lu; Paradkar, Sukanya; Osrin, David; Daruwalla, Nayreen; Cislaghi, Beniamino
Abstract : Transforming communities into supportive environments for women facing risks of violence requires community members to play an active role in addressing violence against women (VAW). We did a grounded theory study of enablers and barriers to community response to ongoing violence, sampling from programme areas of a non-governmental organisation (NGO)-led community mobilisation intervention in informal settlements in Mumbai, India. We held 27 focus group discussions and 31 semistructured interviews with 113 community members and 9 NGO staff, along with over 170 hours of field observation. We found that residents responded to violence in diverse ways, ranging from suicide prevention to couple mediation to police and NGO referral. Enabling and constraining factors fit into a social ecological model containing intrapersonal, immediate social network, and wider societal levels. We identified four themes interlinking factors: legitimacy of action, collective power, protection against risk and informal leadership. Legitimacy of action was negotiated in the context of individual disputes, making community members question not only whether VAW was 'wrong', but who was 'wrong' in specific disputes. Collective power through neighbourhood solidarity was key to action but could be curtailed by violent gang crime. Interveners in incidents of VAW turned out to need significant physical, social and legal protection against reprisal. However, repeat interveners could become informal leaders wielding influential prosocial reputations that incentivised and facilitated action. Our model integrates multiple perspectives on community action into one analytical framework, which can be used by implementers to ensure that community members receive encouragement, support and protection to act.